Information System Design Library Management At Jakarta Television Station - Yasin, Muhammad; Indah (ENCRYPTION: Journal of Information And Technology, 2024)
Monitoring and management of program material/content on television stations is crucial for it to be run and presented effectively and efficiently. This writing explains the obstacles faced and determines the right solution to overcome each obstacle faced. Using descriptive presentation and data collection methods carried out in the form of literature studies, field studies in the form of observations, interviews and documentation. Based on research, it can be concluded that PT ITV still uses other TV systems to record program data, so that PT ITV has difficulties in monitoring content material, limited access to using this system. Having a computerized Mandiri Library Management system is a must according to PT ITV's needs. In its creation, there were 4 actors/Users in this information system, namely: Programming, Library, QC (Quality Control), and MCR (Master Control Room). Programming can input the program Playlist, the Library can manage the program Playlist data, QC can check and make status changes, and MCR can see the daily Playlist that is ready to be broadcast.